Copiers and Copy Printers from Gestetner - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
Gestetner, UK has brought out a range of office products in the market for various categories of users. Copiers There are three models of copiers which can accept sheets, books and 3dimensional objects upto A3 size, and give output from A3 to A6 size paper. The model 231 5 can accept paper from 64-80 gsm and give 15 A4 size copies per minute. It can zoom from 48 to 205 per cent in 1 per cent increments. Model 2321 can give 21 copies per minute and has preset reproduction ratios for 13 reduction and 9 enlargements besides zoom range. The optionals include Automatic Document Feeder (ADF) for size A3 to A5 having speed of 13 originals per minute, 10 bin sorter and 20 bin sorter with convenience stapler. http://dx.doi.org/10.14429/dbit.14.2.3096